Miss Peregrine's Home for Peculiar Children [compact disc, unabridged] - Riggs, Ransom (Riggs, Ransom. Novel of Miss Peregrine's Peculiar Children., 2011)
After a family tragedy, Jacob feels compelled to explore an abandoned orphanage on an island off the coast of Wales, discovering disturbing facts about the children who were kept there.